THE APPLICATION OF TEACHING OF PARTICIPATION IN THE ROBBING CRIMINAL ACT - Basri Basri; Johny Krisnan (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain 1) Who are the parties that can be used as a suspect and how its position legally; 2) A criminal offence if the supposition to perpetrators. This study is a normative legal and empirical legal research. The results of the study that "participation teachings" in the case of Zakia Arifin Binti Zainal Arifin and Mrs. Tuti Ambarwati can be applied. However, there is a difference between the concept of participation in Article 55 of the Criminal Code with the element of cooperating or alliance in Article 363 and Article 365 of the Criminal Code. Article 55 of the Criminal Code is a general rule (legi generali) for acts of inclusion (deelneming) in a criminal act, namely for people who commit, order to do, participate in doing, and who advocate for criminal acts, in which the perpetrators are punished as a person who commits a crime; whereas Article 363 paragraph 1 number 4 of the Criminal Code, is a special rule (lex specialis) that is two people have committed acts of theft, and article 365 (specifically paragraph (2)) of the Criminal Code is a special rule (lex specialis), namely there is a criminal offense for theft with a joint charge (allied).